Therapeutic Opportunities of Interleukin-33 in the Central Nervous System - Sun, Yun; Wen, Yankai; Wang, Luxi; Wen, Liang; You, Wendong; Wei, Shuang; Mao, Lin; Wang, Hao; Chen, Zuobing; Yang, Xiaofeng (Frontiers in Immunology, 2021)
Interleukin-33 (IL-33), a member of the IL-1 cytokine family, is involved in various diseases. IL-33 exerts its effects via its heterodimeric receptor complex, which comprises suppression of tumorigenicity 2 (ST2) and the IL-1 receptor accessory protein (IL-1RAP). Increasing evidence has demonstrated that IL-33/ST2 signaling plays diverse but crucial roles in the homeostasis of the central nervous system (CNS) and the pathogenesis of CNS diseases, including neurodegenerative diseases, cerebrovascular diseases, infection, trauma, and ischemic stroke. In the current review, we focus on the functional roles and cellular signaling mechanisms of IL-33 in the CNS and evaluate the potential for diagnostic and therapeutic applications.